MODEL PERSAMAAN STRUKTURAL (STRUCTURAL EQUATION MODEL) PENGUJIAN MODEL HUBUNGAN SOCIAL IDENTITY DENGAN GROUP DECISION MAKING - Yahya, Yahya (ULUL ALBAB Jurnal Studi Islam, 2011)
This article examines the model theory of out-group threaths, Social Identity and Group Decision Makings and finds out the contribution of out-group threaths and Social Identity toward the decision makings process by applying structural equation model, AMOS 6. Results showed that while out-group threats are salients influenced the positive of social identit which affected to the group decision making process.Â  These findings support previous research conducted by Thompson dan Kray (1998) found that there is a positive relations between social identity and group decision making.